EVALUATION OF BEAN VEGETABLE SAMPLES ON PRODUCQ TIVITY AND ROOT FORMATION CAPACITY IN THE CONDIQ TIONS OF FORESTQSTEPPE OF THE OB REGION - O. V. Parkina; N. S. Harina (Овощи России, 2015)
The efficiency of root formation capacity of the bean hybrids in the conditions of forest,steppe  of the Ob region has been shown.